Uma proposta metodológica para avaliação de bibliotecas digitais: usabilidade e comportamento de busca por informação na biblioteca digital da Puc-Minas - Paula Bohmerwald (2003)
Recently, with the development of the Internet, new systems and information sources have been created, moving the user to a new context of information seeking. Considering this, authors of Information Science and Computer Science have been studying about interaction between users and systems in this new environment. Thus, this work proposes the complementary and simultaneous use of methodologies in both areas, aiming a better evaluation of an information system. To test the proposed methodology this research is conducted at the Digital Library of Theses and Dissertations of the Catholic University of Minas Gerais, Brazil. Initially, this work presents methods of web sites usability evaluation and models of information seeking behavior. Based on these methods and models, the data collecting was divided into five steps: (1) Demographic questionnaire; (2) Usability testing; (3) Satisfaction questionnaire; (4) Study of information seeking behavior using a free navigation test and (5) Log analysis. The results of each step are presented, discussed and compared, in order to analyze and to suggest improvements for the digital library. At last, the results are confronted in order to evaluate the contribution of each step to the analysis of the case study and are also compared with others resulted studies about Digital Libraries usability.